Money Laundering Kejahatan Trans Nasionaldan Urgensi Penanggulangannya - syahrudin (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2021)
Abstract In the era of globalization, the problem of money laundering is becoming increasingly widespread because the existence of this crime involves many factors that cross national boundaries. The problem of money laundering is the dark side of globalization. Handling money laundering cannot be solved quickly and easily, but it takes time, commitment, political will, and support from all parties: national governments, communities, and multilateral cooperation. Learning from South Korea, Indonesia and the international community, for example, requires bureaucratic reform based on a more efficient structure by upholding the spirit of 'Good Governance' and 'Check and Balance' which is expected to encourage all elements of the nation to work together to solve corruption at a practical level. In addition, the judiciary must be consistent and responsible in enforcing the rule of law in a professional and impartial manner. The key to law enforcement lies in synergistic cooperation between the police, prosecutors, and the judiciary. At the global level, effective global governance is very important for eradicating corruption and money laundering. Multilateral cooperation needs to be improved and made effective in handling issues related to transnational organized crimes, such as corruption and money laundering. Seeing the very detrimental impact of the practice of money laundering globally, especially the effect that can damage the country's economic resilience, of course, effective efforts are needed to eradicate its development. Some things that can be suggested to eradicate money laundering practices are as follows: (1) Good coordination between sectors and between domestic departments in implementing anti-money laundering regulations and policies issued by the government. (2) Improvements in the cultural aspects of law enforcement and government officials, as well as financial and banking institutions are also very much needed to reduce opportunities for bribery committed by money laundering actors. (3) It is necessary to have a minimum standard that is acceptable at the international level regarding anti-money laundering, both in financial and banking regulations, corporate law and legal aid between countries. A standard international law must be made so that it becomes a benchmark for countries in the world. (4) A strong commitment is needed from the governments of countries in the world to eradicate money laundering practices, thereby facilitating bilateral and multilateral cooperation within the framework of supranational institutions to combat money laundering globally. With the existence of a united global community to eradicate money laundering, the interests of certain countries that could hinder the process of implementing the eradication of money laundering can be suppressed.